Agricultural water reuse in low-income settings: health risks and risk management strategies - Keraita, Bernard N.; Drechsel, Pay (2016)
Wastewater may be defined as the combination of liquid wastes discharged from domestic households, farms, institutions, and commercial and industrial establishments eventually mixed with groundwater, surface water, and stormwater. Wastewater is increasingly receiving global attention as it is seen as one of the alternative solutions to increasing global water scarcity. Indeed, wastewater is globally being reused in many applications including groundwater recharge, industrial reuse like for cooling, environmental and recreational uses, nonpotable urban uses, and indirect or direct potable reuse. However, agricultural irrigation and landscaping is by far the largest wastewater use sector. Indeed, millions of farmers worldwide are involved in wastewater irrigation activities. However, wastewater contains a variety of pollutants and contaminants, which may pose health risks if not well managed. These pollutants include salts, metals, metalloids, pathogens, residual drugs, organic compounds, endocrine disruptor compounds, and active residues of personal care products. The kind and extent of health risks depend on many factors including the types and levels of contaminants as well as regional risk relevance. In low-income countries, risks from pathogens receive the most attention. This is because people in these countries are most affected by diseases caused by poor sanitation such as diarrheal diseases and helminth infections, so high loads of pathogenic microorganisms are often found in wastewater systems. Focusing on low-income contexts, this chapter presents health risks posed by wastewater irrigation activities and some practical examples on how these risks could be managed.